2013
DOI: 10.18697/ajfand.56.12590
|View full text |Cite
|
Sign up to set email alerts
|

Shelflife of whole fresh lake Malawi tilapia (Oreochromis species - Chambo) stored in ice

Abstract: Lake Malawi Tilapia (chambo) fish species is widely consumed and forms the most important commercial fishery in Lake Malawi. However, as a highly perishable commodity, knowledge regarding how long fresh fish would remain in acceptable and safe condition in storage is indispensable for consumers and processors. Presently, no such information exists for the Lake Malawi Tilapia in Malawi. A study was therefore conducted to estimate shelflife of whole fresh Lake Malawi Tilapia stored in ice (0 o C) for 21 days. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Values for nutrient composition of the fresh fish in this study were close to those reported earlier by Kapute et al [7] for fresh Lake Malawi tilapia confirming that the fish is rich in protein. Significant changes in the nutrient values of the fish after being subjected to different types of cooking methods were observed, and these, therefore, echo many earlier reports that processing compromises the nutritional quality of fish [2,4,5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Values for nutrient composition of the fresh fish in this study were close to those reported earlier by Kapute et al [7] for fresh Lake Malawi tilapia confirming that the fish is rich in protein. Significant changes in the nutrient values of the fish after being subjected to different types of cooking methods were observed, and these, therefore, echo many earlier reports that processing compromises the nutritional quality of fish [2,4,5].…”
Section: Discussionsupporting
confidence: 91%
“…Lake Malawi tilapia (O. karongae) is the most commonly consumed cooked food fish sold in Malawi. While some information is available regarding the nutritive values of raw (unprocessed) Lake Malawi tilapia [6,7], this information is lacking for fish processed using different cooking methods. The present study was, therefore, carried out to investigate the effects of different cooking methods (boiling, roasting, pan frying, and the use of a traditional fireless cooker) on the proximate and mineral composition of O. karongae (Lake Malawi tilapia).…”
Section: Introductionmentioning
confidence: 99%
“…Ndunduma is among lean fish species which are generally considered to contain high ash levels [25]. Results generally showed an increase in the ash content of the processed samples agreeing with earlier studies [9] that ash content increases with dry processing in fish.…”
Section: Discussionsupporting
confidence: 89%
“…Bacterial counts obtained near the end of storage can be considered as low compared to those obtained in other freshwater species (Chytiri et al, 2004;Scherer et al, 2006;Li et al, 2012;Kapute et al, 2013) and also marine species (Hozbor et al, 2006;Ӧzogul et al, 2006Ӧzyurt et al, 2009;Sant'Ana et al, 2011). This can be explained by several intrinsic and extrinsic factors that influence the microbial capacity to invade and develop in the muscle and, consequently, the spoilage rate and the shelf life of the product (Huss, 1998).…”
Section: Microbial Changesmentioning
confidence: 99%